PRELIMINARY EVALUATION OF THE ACARICIDAL ACTIVITY OF VITEX NEGUNDO LINN. (LAGUNDI) SOLVENT EXTRACT/FRACTIONS AGAINST RHIPICEPHALUS SANGUINEUS SENSU LATO LARVAE (LATREILLE 1806) - Ong, Perkin Charles Nemenzo; Pradera, Carl Leonard Monreal; Bagot, Melvin Ayes (Journal of Agriculture and Technology Management; Vol 21 No 2 (2018): Journal of Agriculture and Technology Management (JATM) Volume 21 July - December 2018 Issue, 2019)
The acaricidal activity of Vitex negundo was determined with the use of hexane, 95% ethanol and water as solvents against larvae of Rhipicephalus sanguineus sensu lato. Dried V. negundo leaves were sequentially extracted and each filtrate (crude hexane extract or CHE, crude ethanolic fraction or CEF and crude aqueous fraction or CAF) was concentrated with a rotary evaporator. There were different computed concentrations of the solvent/fractions and were used against the larvae through spraying method. Each treatment of the solvent/fractions was replicated three times with at least 10 larvae (ranges from 10-29) and the mortality was observed on 12th and 24th h exposure; death of the larvae were confirmed through prodding with toothbrush bristle. The highest acaricidal activity that has been recorded in this study were 46.09% for 100% CHE, 54.79% for 11.22% CEF and 57.43% for 33.66% CAF; with the LC 50 of 16.10% and 31.91% for CEF and CAF, respectively. The results of this study indicated that the acaricidal activity of V. negundo extract and fraction against larvae are not effective based on European Agency for the Evaluation of Medicinal Products and as compared to the commercially available acaricide. Perhaps increasing the concentrations of the CEF and CAF could be possibly done for higher mortality of the R. sanguneus sensu lato larvae.